Italian Laced-Case Paper Bindings. Issue 1 (2nd October 2019) - Pickwoad, Nicholas
ABSTRACT: The history of Italian laced-case bindings with covers of cartonnage can be traced back to the early sixteenth century, but the so-called legatura alla rustica achieved its definitive form in the seventeenth century, from which time they became one of the most common types of retail binding in the Italian booktrade. This article looks at the development in Italy of this type of binding and the different features that can be found on them from the first decade of the sixteenth century to the end of the eighteenth, and examines the ways in which a very cheaply-made binding was cleverly designed to exploit the unique characteristics of textblocks made from hand-printed sheets of handmade paper and the extraordinary qualities of Italian cartonnage to allow very light-weight and rapidly executed bindings to be remarkably durable. The economy of their manufacture is evidenced through the way paper was used to make the endleaves and the production of the cartonnage covers in format-related sizes to reduce waste. The article ends with four appendices which contain detailed descriptions of 16 representative examples, a fifth appendix which lists different ways in which binders sought to reinforce the structures of these bindings and a final appendix listing the sizes of 25 covers made from whole sheets of cartonnage.